2004
DOI: 10.4314/eamj.v80i10.8755
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic pattern of thyroid disease

Abstract: Background: Diseases of the thyroid are manifested by alteration in hormone secretion, enlargement of the thyroid gland (goiter), or both. The principal diseases of the thyroid gland are goiter (diffuse or nodular), hypo or hyperthyroidism, thyroiditis and neoplasms. The incidence and prevalence of these thyroid diseases in a given community are variable depending on various factors. Simple (non-toxic) goiter is extremely common throughout the world and is most prevalent in mountainous areas. The reported prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
70
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 1 publication
20
70
2
Order By: Relevance
“…1 The reverse is seen in Africa where autoimmune hypothyroidism is rarely encountered, either by clinicians 18,19 or histopathologists. 17 In striking contrast to Graves' disease, the incidence of autoimmune hypothyroidism in African blacks does not appear to have been amplified by improvements in iodine intake. One possible explanation for this discrepancy may lie with recognition.…”
Section: Autoimmune Hypothyroidismmentioning
confidence: 96%
See 1 more Smart Citation
“…1 The reverse is seen in Africa where autoimmune hypothyroidism is rarely encountered, either by clinicians 18,19 or histopathologists. 17 In striking contrast to Graves' disease, the incidence of autoimmune hypothyroidism in African blacks does not appear to have been amplified by improvements in iodine intake. One possible explanation for this discrepancy may lie with recognition.…”
Section: Autoimmune Hypothyroidismmentioning
confidence: 96%
“…[17][18][19] The majority of affected people live within subsistence agricultural systems, commonly in mountainous regions which have been deprived of iodine by leaching of the soil. Goitrogens in local foods like cassava and millet accentuate the effects of iodine deficiency 20 and other micronutrient deficiencies such as selenium also play a role in the development of goitres.…”
Section: Endemic Goitrementioning
confidence: 99%
“…Similar female preponderance was noted by Unnikrishnan et al 9 As reported by Tsegaye et al 85.7% per cent of the thyroid diseases were found in the age group 20-59 years. 10 In present study, 71.51% cases were in the similar age group.…”
Section: Discussionmentioning
confidence: 59%
“…Numerous small studies from various parts of the nation carried out on the varied populations demonstrate different prevalence rates. [11][12][13] Till now, these are no data reported regarding prevalence of thyroid disorders from Far western population of Nepal and this is the first study which is being reported from this region.…”
Section: Introductionmentioning
confidence: 99%
“…12 Thyroid dysfunction is usually acquired and may occur any time in life and is one of the chronic noncommunicable diseases affecting women more than men. Hypothyroidism and hyperthyroidism are two main thyroid disorders of which hypothyroidism are much more common.…”
Section: Introductionmentioning
confidence: 99%